Capitalul social ca premisă a dezvoltării durabile - Voicu, Bogdan (Calitatea Vieții, 2008)
The paper addresses the issue of social relations, as manifestation of the social capital. The aim is to identify those groups, part of the Romanian society, which may be at risk with regard to the stocks of bridging social capital. Using the Diagnosis of Quality of Life 2006 survey data, three indicators are considered: the frequency of meeting friends, the quality of the relations with family and neighbors, the generalized trust. The study of each of the three indicators contributes to sketching the portrait of those with low sociability, which may be exposed, as argued in the paper, to social marginalization and exclusion.